'News for Everyone? Perspectives of Young People and Journalists on Political Reporting in UK Television'. (May 2014) - Henderson, Lesley
Numerous studies have focused on young people and the extent to which they are politically (dis)connected; but we know far less about how 'young people' are perceived by journalists and editors who 'make' political news. This article reflects on a qualitative study involving focus groups with young adults aged 16–24 years (n = 80) and interviews with television news journalists and editors (n = 26). Young people perceived television news as overly focused on youth crime and anti-social behaviour, finding it difficult to connect mainstream political news with the lived reality of everyday life. Journalists are under considerable pressure to attract young audiences of 'plugged in achievers' and defensive of what they consider to be legitimate focus on 'Westminster' power. The views and occupational practices of political journalists should be studied if we are to shed light on news values that underpin reporting and identify opportunities by which inequities of access can be challenged.